INTEGRASI ISO 9001:2015 DALAM TRANSFORMASI MANAGEMENT MUTU : STRATEGI PENINGKATAN KUALITAS LAYANAN PENDIDIKAN - Faizatun Nafsiyah; Laura Paramita; Suratman Suratman (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2025)
Quality management transformation is an urgent need for schools to meet the demands of improving the quality of education in the era of globalization and the Industrial Revolution 4.0. ISO 9001:2015 is an international standard that provides a systematic, structured, and customer-satisfaction-oriented framework for teaching. This article aims to analyze the integration of ISO 9001:2015 into the quality management system at SMP YPPSB Sangatta Utara and to evaluate its impact on improving the quality of educational services. Using a qualitative approach with a case study design, data were collected through in-depth interviews, field observations, and documentation, and analyzed interactively through the stages of data condensation, data presentation, and verification of results until data saturation was achieved. The results show that implementing ISO 9001:2015 has brought significant changes in school governance, marked by increased consistency in the learning process, greater administrative discipline, greater transparency in information, and the strengthening of a quality culture through the Plan–Do–Check–Action (PDCA) cycle. In addition, continuous monitoring through internal quality audits encourages improved service and school accountability. The integration of these standards has also resulted in increased parent satisfaction, teacher engagement, and data-driven decision-making. However, challenges remain, such as high administrative burdens and uneven understanding of standards across all educators. Continuous improvement efforts are being implemented through training, enhanced digital documentation, and optimized roles for the quality management team. Thus, the implementation of ISO 9001:2015 has proven effective in strengthening school quality management and is a worthy model for other educational institutions, particularly in developing regions.